2016
DOI: 10.1186/s13006-016-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices on postnatal wards in urban and rural areas of the Deyang region, Sichuan province of China

Abstract: BackgroundDespite the efforts that have been made to promote breastfeeding in China since the 1990s, there is still a very low prevalence of exclusive breastfeeding. The objective of this study was to assess the current situation of infant feeding practices during the postpartum hospital stay in urban and rural areas of the Deyang region.MethodsCross-sectional sampling was used in two urban hospitals and five rural clinics in the Deyang region of southwestern China. Interviews with mothers after delivery (urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…Perceived insufficiency of breastmilk was mentioned by 13 women (4.6%) as reason for making use of other milk substitutes in addition to breastmilk, similarly 5.7% named insufficient breastmilk as decisive point of introducing CF. Consistent with this finding perceived insufficiency of milk was a major reason for non-exclusive breastfeeding, or delayed initiation of breastfeeding in other Indian studies [55][56][57], and has been also shown to be a major reason for low ExcBF rates among Chinese mothers [58].…”
Section: Breastfeeding Practicessupporting
confidence: 84%
“…Perceived insufficiency of breastmilk was mentioned by 13 women (4.6%) as reason for making use of other milk substitutes in addition to breastmilk, similarly 5.7% named insufficient breastmilk as decisive point of introducing CF. Consistent with this finding perceived insufficiency of milk was a major reason for non-exclusive breastfeeding, or delayed initiation of breastfeeding in other Indian studies [55][56][57], and has been also shown to be a major reason for low ExcBF rates among Chinese mothers [58].…”
Section: Breastfeeding Practicessupporting
confidence: 84%
“…Some of the previous studies used knowledge scores on breastfeeding benefits as a predictor of breastfeeding practice, but they failed to provide consistent evidence on its association with EBF. 11 18 However, we only focused on the key message that infants should be exclusively breastfed for the first 6 months. This implies that future education intervention projects should pay more attention to disseminating core messages in promoting optimal breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature in China disclosed the disparities in breastfeeding practices between urban and rural areas, 3 11 employed and unemployed mothers, 12 Han and other minority groups, 13 and highly educated and less-educated mothers. 14 A wide range of individual, sociodemographic, cultural, psychosocial and environmental factors had been identified as risk factors of EBF in China, 15 16 such as maternal and child characteristics, 12 13 17–19 support from family members and friends, 18 20 21 maternity facility education, support and practice 11 17 19 22 as well as breastfeeding intention. 18 Yet, few studies have examined the difference in breastfeeding practice and its predictors among migrant and non-migrant mothers in China.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to understand how best to target education activities for women who live in both urban and rural areas for breastfeeding practices. Other studies in Asia have also found higher levels of exclusive breast-feeding in rural compared with urban areas (27,33) . This could be related to labour force participation, as other studies have found that women who occupied management/supervisory jobs were more likely Table 2 Breast-feeding rates among 18-49-year-old women with a child under 2 years of age according to receipt of a community-level breast-feeding promotion intervention on breast-feeding practices, Myanmar, August-September 2016 Analysis time (months) Survival probability Fig.…”
Section: Discussionmentioning
confidence: 80%